Characterizing sarcoma dominance pattern in uterine carcinosarcoma: Homologous versus heterologous element. (September 2018) - Matsuo, Koji; Takazawa, Yutaka; Ross, Malcolm S.; Elishaev, Esther; Yunokawa, Mayu; Sheridan, Todd B.; Bush, Stephen H.; Klobocista, Merieme M.; Blake, Erin A.; Takano, Tadao; Baba, Tsukasa; Satoh, Shinya; et al.
Abstract: Objective: To examine significance of sarcoma dominance (SD) patterns in uterine carcinosarcoma (UCS). Methods: This is a secondary analysis of multicenter retrospective study examining women with stages I-IV UCS who underwent primary surgery. SD was defined as >50% of sarcoma component in uterine tumor. SD patterns were grouped as homologous sarcoma without SD (homo/non-dominance, n = 351), heterologous sarcoma without SD (hetero/non-dominance, n = 174), homologous sarcoma with SD (homo/dominance, n = 175), and heterologous sarcoma with SD (hetero/dominance, n = 189), and correlated to tumor characteristics and survival. Results: SD patterns were significantly associated with age, body habitus, carcinoma type, tumor size, depth of myometrial invasion, and nodal metastasis (all, P < 0.05). On univariate analysis, SD was associated with decreased progression-free survival (PFS) and cause-specific survival (CSS) in homologous cases (both, P < 0.05) but not in heterologous cases. On multivariate models, both homologous and heterologous SD patterns remained independent prognostic factors for decreased PFS (adjusted-hazard ratio [HR] ranges: homo/dominance 1.35–1.69, and hetero/dominance 1.47–1.64) and CSS (adjusted-HR ranges: 1.52–1.84 and 1.66–1.81, respectively) compared to homo/non-dominance (all, P < 0.05). Among stage I-III disease, when tumors had SD, adding radiotherapy to chemotherapy was significantly associated with improved PFS (adjusted-HR: homo/dominance 0.49, and hetero/dominance 0.45) and CSS (0.36 and 0.31, respectively) compared to chemotherapy alone (all, P < 0.05); contrary, this association was not observed with absence of SD (all, P > 0.05). Conclusion: In UCS, SD impacts survival in homologous but not in heterologous type. Regardless of sarcoma types, SD was associated with decreased survival in UCS; adding radiotherapy to chemotherapy may be an effective postoperative strategy.